The effect of an mHealth intervention for titration of insulin for type 2 diabetes: A pilot study. (June 2020) - Bramwell, Siân E; Meyerowitz-Katz, Gideon; Ferguson, Caleb; Jayaballa, Rajini; McLean, Mark; Maberly, Glen
Background: Stabilising blood glucose levels (BGL) after starting or changing insulin and related therapies can be challenging for diabetes services and the patient with type 2 diabetes. Traditionally, a credentialled diabetes educator (CDE) would talk with the patient over the phone to obtain a history of their BGLs over the previous week and provide advice on the insulin dose adjustments as required. This study trialled a smartphone application for sharing BGLs, with the ability to digitally transmit advice back to patients compared with their usual care. Aims: The aim of this study was to compare desirability, efficiency and ease of use. Methods: Participants were enrolled in either the traditional ( n =50) or Health2Sync (H2S) ( n =42) treatment group by patient preference. All insulin stabilisations were conducted by the CDE. Descriptive statistics were used for analysis. Results: The average total time taken to titrate patients was similar in both groups ( p >0.05), however there were fewer failure of contacts reported with H2S ( p <0.01) and time per interaction was also lower ( p <0.01). Sensitivity analysis revealed that, excluding the influence of no contacts, H2S patients had a lower average time for titration ( p <0.01). There was no difference in clinical outcomes as measured by HbA1c between the two groups ( p =0.75). Conclusion: We demonstrated a high acceptance and clinical utility of the H2S application. Clinicians were happy to use H2S and found it easy and convenient for most patients. Importantly, this reduced frequency of contacts with patients, time per interaction and average time for titration ( p <0.01). Patient selection for this communication intervention is important.